Preparation and Quality Evaluation of Orange Incorporated Paneer Whey- Lemon Beverage - Gautam, Hemant; Sigdel, Manish (Journal of Food Science and Technology Nepal, 2022)
The main objective of this study was to utilize the paneer whey for the preparation of beverage. For this purpose, orange juice, lemon juice and paneer whey (obtained by 2% citric acid coagulation) were prepared. After screening experimental beverages made using mixture design by sensory analysis, a control sample and four different samples were prepared, varying proportion of whey and orange juice, while keeping lemon juice and sugar content at fixed level of 1% v/v and 8% w/v, respectively. Then, the whole mix was heated at 88ºC for 15 minutes, after filling in glass bottles, then cooled to room temperature at 25±5ºC and were subjected to sensory evaluation and chemical analysis. The best beverage formulation was determined from higher sensory score and higher ascorbic acid content and stored at refrigeration temperature 6±1ºC. The ascorbic acid content of the four beverage formulations prepared by varying orange juice at the level 10% (sample A), 12.5% (sample B), 15% (sample C) ,17.5% (sample D) and control sample E (0% orange juice) was determined. Statistically there was no significant difference (p ≤ 0.05) in between the samples C and D with respect to ascorbic acid content. From 9-point hedonic rating sensory analysis, the best formulated orange incorporated paneer whey-lemon beverage sample was found to be sample C having 76% whey, 15% orange juice, 1% lemon juice and 8% sugar. The TSS, pH, acidity, reducing sugar, total sugar, and ascorbic acid content of this optimized beverage sample was found to be 12 ± 0.1 ºBx, 4.35 ± 0.05, 0.40 ± 0.01%, 5.04 ± 0.07%,11.65 ± 0.24% and 4.58 ± 0.51 mg/ 100 ml, respectively.